INEDITHOS: a Hospital Pedagogy project devoted to improving the quality of life of children and young people with rare diseases from the intervention, and research with university volunteering. - Francisca NEGRE BENNASAR (Ediciones Universidad de Salamanca, 2018)
This paper presents an experience in Hospital Pedagogy organized by the University of the Balearic Islands. This project is called INEDITHOS and its main objective is to work into improve the quality of life of children and youth with Rare Diseases. The project works in three lines of intervention: psycho-pedagogical support to patients and their families, research to respond to the needs that are detected in this area and the training of university students who collaborates in the project, using the Service Learning methodology. The long trajectory of the project that began in 2003 has made it possible to consolidate the three interventions resulting in a non-profit association with the same name. This result is complemented by the growing involvement of other Associations such as ABAIMAR and FEDER with which close collaboration is maintained. It is also worth noting the increase in the number of volunteers, which allows to offer attention to a higher number of affected while improving the quality of the interventions made thanks to the collaboration and involvement of students and teachers who, through the methodology of Learning and Service, carry out activities and elaborate end-of-degree and master's work based on the needs identified in the volunteer interventions. INEDITHOS has introduced Rare Diseases in the university context sensitizing a large part of the Educational Community.